Executive summary of 'Re-examining the place of servicescape in marketing: a service-dominant logic perspective'. Issue 5 (19th August 2014) - Beal, Brian; Martin, Charles; Fall, TansyMarie
<x content-type="archive" xml:space="preserve">Abstract</x>